1984
DOI: 10.2527/jas1984.592498x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Endocrine Regulation of Metabolism during Lactation

Abstract: Lactogenesis signals the shift from uterine nutrient transfer to the fetus to neonatal nourishment at the mammary gland. Metabolic adaptations involved in this process are under endocrine regulation. Key events include an increase in blood flow to mammary tissue, a decrease in nutrient utilization by peripheral tissues and an increase in nutrient utilization by mammary tissue for milk synthesis. Deficits of certain substrates during early lactation require mobilization of those substrates from depot stores. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
9

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 72 publications
2
54
1
9
Order By: Relevance
“…Une tendance à la lipomobilisation a toutefois été observée dans certaines expériences de longue durée (Soderholm et al, 1986a, b Emery, 1973 ;Convey, 1974 ;Patterson et Linzell, 1974 ;Bauman, 1976 ;Swan, 1976 ;Coggins et Field, 1978 ;Hart et al, 1978Hart et al, , 1979Miller et al, 1978 ;Cowie et al, 1980 ;Walsh et al, 1980 ;Trenkle, 1981 ;Blum et al, 1982Blum et al, , 1983Blum, 1983, Mc Dowell, 1983Bitman et al, 1984b ;Collier et al, 1984 ;Refsal et al, 1984 ;Aceves et al, 1985 ;Akasha et al, 1985 ;Frohli et Pethes et al, 1985 ;Plaut et al, 1985 ;Thilsted, 1985b ;Bauman et Mc Cutcheon, 1986 ;Gerloff et al, 1986bJ. Les réponses de la sécrétion d'hormone de croissance à la sous-alimentation (revue de Vernon, 1980) ou à la gestation (Koprowski et Tucker, 1973) (Collier et al, 1984). La mobilisation des protéines corporelles (revue de Chilliard et al, 1983) Van den Bergh, 1972 ;Metz et al, 1974 (Little, 1974 ;Rowlands, 1978 ;Treacher, 1978 ;Larnicol et al, 1984).…”
Section: Préambuleunclassified
“…Une tendance à la lipomobilisation a toutefois été observée dans certaines expériences de longue durée (Soderholm et al, 1986a, b Emery, 1973 ;Convey, 1974 ;Patterson et Linzell, 1974 ;Bauman, 1976 ;Swan, 1976 ;Coggins et Field, 1978 ;Hart et al, 1978Hart et al, , 1979Miller et al, 1978 ;Cowie et al, 1980 ;Walsh et al, 1980 ;Trenkle, 1981 ;Blum et al, 1982Blum et al, , 1983Blum, 1983, Mc Dowell, 1983Bitman et al, 1984b ;Collier et al, 1984 ;Refsal et al, 1984 ;Aceves et al, 1985 ;Akasha et al, 1985 ;Frohli et Pethes et al, 1985 ;Plaut et al, 1985 ;Thilsted, 1985b ;Bauman et Mc Cutcheon, 1986 ;Gerloff et al, 1986bJ. Les réponses de la sécrétion d'hormone de croissance à la sous-alimentation (revue de Vernon, 1980) ou à la gestation (Koprowski et Tucker, 1973) (Collier et al, 1984). La mobilisation des protéines corporelles (revue de Chilliard et al, 1983) Van den Bergh, 1972 ;Metz et al, 1974 (Little, 1974 ;Rowlands, 1978 ;Treacher, 1978 ;Larnicol et al, 1984).…”
Section: Préambuleunclassified
“…In addition, Collier et al [3] suggested that the increase in the adrenergic receptor population in adipose tissue when lactogenesis occurs results in an increase in epinephrine-stimulated fatty acid release, and consequently, in an increase in circulating plasma NEFA. According to Neil [20] and Le Cozler et al [14], the level of circulating urea mainly reflected the feed intake of the sow, rather than protein mobilization. Thus, the lower concentration of urea observed on the day of parturition compared with the values observed before or after farrowing, was, then, most likely the result of the low feed intake.…”
mentioning
confidence: 99%
“…As women [23,24], rats [25], cows, and sheep [26,27] have a state of relative hypothyroidism during lactation, with levels of circulating T3 and T4 significantly lower [28], this condition may explain the decrease in circulating T4 in the mare of this case report.…”
Section: Discussionmentioning
confidence: 94%